2006
DOI: 10.1016/j.drugalcdep.2005.10.010
|View full text |Cite
|
Sign up to set email alerts
|

The role of the early therapeutic alliance in predicting drug treatment dropout

Abstract: Background: To investigate the role of the therapeutic alliance in predicting length of retention in residential drug treatment. Methods:The study recruited 187 clients starting residential rehabilitation treatment for drug misuse in three UK services. Counsellor and client information was assessed at intake, and the average total scores of client and counsellor ratings on the WAI-S (obtained during weeks 1 to 3) were use as the alliance measure. Length of retention and treatment completion (stay beyond 90 day… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
84
0
9

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 128 publications
(99 citation statements)
references
References 47 publications
6
84
0
9
Order By: Relevance
“…These findings are consistent with work that found that a collaborative relationship is related to treatment retention for drug abuse, 38,39 alcohol abuse, 40 and family therapy. 41 Implementing such interventions in safety net hospitals can help decrease the problems of no-shows and increase retention in care of minority populations that have been linked to service disparities.…”
Section: Discussionsupporting
confidence: 82%
“…These findings are consistent with work that found that a collaborative relationship is related to treatment retention for drug abuse, 38,39 alcohol abuse, 40 and family therapy. 41 Implementing such interventions in safety net hospitals can help decrease the problems of no-shows and increase retention in care of minority populations that have been linked to service disparities.…”
Section: Discussionsupporting
confidence: 82%
“…Confidence in professional competence may occur when there is a good quality patient-counsellor relationship. The beneficial effect of the therapeutic alliance in the treatment of substance abuse has been documented in previous research (Allen & Olson, 2015;Meier, Barrowclough, & Donmall, 2004;Meier, Donmall, McElduff, Barrowclough, & Heller, 2006;Urbanoski, Kelly, Hoeppner, & Slaymaker, 2012). Direct comparisons of satisfaction scores between studies are problematic due to the diversity of patient populations and treatment settings and the use of overall satisfaction measures.…”
Section: Discussionmentioning
confidence: 99%
“…stronger predictor of drop-out than patient-rated therapeutic alliance (Meier et al, 2006). Willingness to discuss mental health issues with a doctor is also predicted largely by the perceived helpfulness of that doctor, and in turn trust in the doctor and the medical profession.…”
Section: Box 2 Hypothetical Patient's Perspective Of Non-attendancementioning
confidence: 95%